Rapid SO2 gas removal using MgO/AC /CaCO3/Zeolite nanocomposite at room temperature - Ghobad Behzadi pour; Maryam Kamel Oroumiyeh; Leila Fekri aval (Case Studies in Chemical and Environmental Engineering)
The rising population and the expansion of urban areas are leading to heightened energy demands, which are predominantly met through fossil fuel sources. The operation of combustion facilities generates detrimental flue gases, thereby necessitating investigations into methods for controlling emissions to safeguard public health and protect the environment. The adsorbent method of removing pollutant gases involves selecting the proper material, preparation of the adsorbent layer, understanding adsorption mechanisms, contact time, and monitoring levels of pollutants. Various types of adsorbent materials are utilized, including active carbon (AC), zeolites, and metal oxides; each has different properties that affect the efficiency of pollutant removal. This research examined the MgO/AC/CaCO3/Zeolite nanocomposite for SO2 gas removal. The characterization of the adsorbent layer was conducted using X-ray diffraction (XRD), scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) analysis techniques. The findings demonstrated a swift decline in SO2 level, which decreased from 153 ppm to 15 ppm in a short time of 5 minutes. The MgO/AC/CaCO3/Zeolite film can considerably remove the SO2 gas with an efficiency of 92 % at room temperature. The adsorbent film exhibited an adsorption capacity of 133 mg g−1 within 5 minutes. The results of this study provide important insights into the removal of SO2 gas by using adsorption layers, demonstrating the potential of MgO/AC/CaCO3/zeolite nanocomposites as effective materials for air pollution control. This nanocomposite can effectively reduce SO2 with fast adsorption time. As air quality standards continue to be tightened around the world, innovative materials can play a significant role in reducing harmful emissions from industrial sources.